Realising research modes of learning for Masters by coursework using state-based clusters : Final report for a National Teaching Fellowship 2014-2015. - Willison, John (Australia. Dept of Education and Training (DET), 2018)
This Fellowship drew together educators from a variety of backgrounds to ‘hothouse’ the development of pedagogies suitable for the research components of Masters-by-coursework degrees. In keeping with AQF Level 9, Masters-by-coursework programs are required to have enhanced research components. The inclusion of large project-based units, or distributed research-based scholarship, in many Masters-by-coursework programs has raised issues, including: the role of educators in facilitating research-based learning requirements for Masters courses with large enrolments; the role of content-rich courses in preparing students for research-focused projects; the risk of low rates of student progression and completion, especially students (including international students) who completed highly structured and guided undergraduate degrees; and low levels of student preparedness for Ph.D. study following the completion of a Masters-by-coursework degree. The resulting Research Skill Development (RSD) framework is a scaffold that assists academics in appropriately structuring research activities for students at undergraduate level. The framework can be used to support the development of students' research skills, from primary school to PhD levels. [Publisher summary, ed]